Current Concepts in Management of Pterygium - Anuj Bahuva; Srinivas K Rao (Delhi Journal of Ophthalmology)
The pterygium is a common ocular disorder. Medical therapy is ineffective and the goals of surgery are complete removal of the lesion and the prevention of recurrence. Although a wide variety of treatment modalities are currently available, there is no consensus on the ideal option. Pterygium excision is often combined with conjunctival autograft, mitomycin C, beta-irradiation or other adjunctive therapies to reduce recurrence rates. Although studies report the success rates with these approaches, variable inclusion criteria, differences in follow-up and definition of recurrence make comparison of outcomes difficult. This article reviews the current options availablefor the management of Pterygium, reviews the outcomes and suggests guidelines for various categories of the lesion encountered in clinical practice.